EVALUATING THE EFFECTS OF A BOARD GAME IN COGNITION IN LEARNING SHIPPING MANAGEMENT FOR HIGHER EDUCATION - Shanizan Herman Mohd Radzi; Wee Hoe Tan; Amri Yusoff (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
This study proposes the use of board games for teaching and learning shipping management in higher education and examines its effects on cognition. It employs a game-based learning approach to engage students with real-life experience in shipping management so that students are able to experiment with the causes and effects of their decisions based on the theory they have learned. An instance of a shipping management game was developed from the board game framework which stands on the discreet event simulation of a realistic shipping process and activity. A quasi-experimental research design was adopted to measure the effectiveness of the board game in giving students some understanding of shipping operations. Data were gathered from a sample of 67 undergraduate students, using a non-equivalent control group design. Students who received the game-based method performed better in the post-test assessment. A performance comparison indicated that there was a difference in students’ achievement for the tramp services and liner services contents. The use of board game aims to expose students to the best learning experience when they immerse themselves in solving problems and making decisions in the game. Moreover, the board game provides a transparent learning space, which encourages students to make knowledge discovery at their own pace in a non-threatening environment.